2015 IEEE International Symposium on Circuits and Systems (ISCAS) 2015
DOI: 10.1109/iscas.2015.7169145
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of subthreshold swing in multichannel tunneling carbon nanotube field effect transistor (MT-CNTFET)

Abstract: Tunnel Field Effect Transistor (TFET) based on Band-to-Band tunneling mechanism is a revolutionary device technology that has a very strong potential to break the thermodynamic barrier of conventional FETs and provide a very steep subthreshold slope. However, TFETs in general suffer from low on-state current (I ON ). We propose a new TFET structure to increase the drain-to-source current of the tunneling device. The design is based on single-walled carbon nanotubes (SWCNTs). The idea is to provide multiple SWC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The tunneling current increases exponentially with increase in tube's diameter . As mentioned by Azzedin D Es‐Sakhi et al, larger CNT diameter leads to larger leakage current, whereas off‐state current decreases as the bandgap decreases. Because the bandgap of CNT material is inversely proportional to the diameter of the tube, SS increases at large diameter as shown in Figure .…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The tunneling current increases exponentially with increase in tube's diameter . As mentioned by Azzedin D Es‐Sakhi et al, larger CNT diameter leads to larger leakage current, whereas off‐state current decreases as the bandgap decreases. Because the bandgap of CNT material is inversely proportional to the diameter of the tube, SS increases at large diameter as shown in Figure .…”
Section: Resultsmentioning
confidence: 90%
“…At low V gs , the current in the device is dominated by the BTBT (band-to-band tunneling) current 14,23 and BTBT devices have the potential to offer a steeper slope at room temperature. 24 It is also observed that as V gs increases, the band bends and the tunneling probability increase. 25 The finding of Figure 2 reflects that one can utilize the gate-controlled tunneling to achieve SS value lower than 60 mV/decade at room temperature.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation